Rheological properties and hydrodynamics of the unstabilized flow of the non-Newtonian fluids in the working channels of moulding equipment - Носко, Сергей Викторович (Technology audit and production reserves, 2015)
The questions related to the rheological behavior of non-Newtonian fluids in channels of forming equipment. Parameters of rheological equation and their dependence on hydro and thermal modes of processing media are obtained as a result of data processing of rheometric research. Selecting the values of shear rate in the flow processing material and the temperature of its heating effect on the modal performance of the molding equipment and reduce energy consumption for its processing. An experimental research of the processes of unregulated movement of non-Newtonian fluids in channels with sharply varying geometry is conducted. It is shown that the length of the hydrodynamic flow stabilization depends on the rheological properties of the medium and the conditions of entry of the forming equipment into the working channels. Information about the characteristics of the flow medium is manifested in the presence of anomalies of viscosity of inertial forces in the flow required for the analysis and calculation of process parameters of high-speed spinning of viscose fibers.